1999
DOI: 10.1063/1.125387
|View full text |Cite
|
Sign up to set email alerts
|

Polymer diodes with high rectification

Abstract: Polymer diodes made using a bilayer of doped poly(3,4-ethylenedioxythiophene) and a semiconducting polymer in a sandwich structure with two low-work-function metals are reported. The conducting polymer layer acted as a modifier of the injection properties of the low-work-function metal, allowing easy hole injection. Upon insertion of the conducting polymer layer, the contact-limited current flow became bulk limited. With this anode, the fabrication of diodes with a rectification ratio of seven orders of magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 23 publications
0
47
1
Order By: Relevance
“…It is common to use a thin layer of LiF between the active layer and the cathode to improve the V oc in polymer solar cells. [5][6][7][8] The role of the submonolayer of LiF has been suggested to be that of protecting the organic layer during metal deposition, modifying the work function of the cathode, and/ or introducing a dipole at the cathode interface, affecting charge injection. [9][10][11][12][13] The possibility to use roll-to-roll printing techniques is the biggest advantage of polymer electronic devices compared with their inorganic counterparts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is common to use a thin layer of LiF between the active layer and the cathode to improve the V oc in polymer solar cells. [5][6][7][8] The role of the submonolayer of LiF has been suggested to be that of protecting the organic layer during metal deposition, modifying the work function of the cathode, and/ or introducing a dipole at the cathode interface, affecting charge injection. [9][10][11][12][13] The possibility to use roll-to-roll printing techniques is the biggest advantage of polymer electronic devices compared with their inorganic counterparts.…”
mentioning
confidence: 99%
“…In all diodes, indium tin oxide (ITO)/poly(3,4-ethylenedioxythiophene) (PEDOT)-poly(styrenesulfonate) (PSS) are used as the bottom electrodes, and PEO/Al or Al are used as the top electrodes. The active layer is the mixing poly((2,7-(9-(2′-ethylhexyl)-9-hexyl-fluorene)-alt-5,5-(4′,7′-di-2-thienyl-2′,1′,3′-benzothiadiazole))-co-(2,7-(9-(2′-ethylhexyl)-9-hexyl-fluorene)-alt-2,5-thiophene)) APFO-5(LBPF3), [22][23][24] and [6,6]-phenyl-C 61 -butyric acid methylester (PCBM) in a stoichiometry of 1:4 (by weight). For comparison, all diodes were prepared and analyzed under the same conditions.…”
mentioning
confidence: 99%
“…In order to fabricate organic diodes on top of the photopatterned resistor cells, we have introduced a commonly used p-type conjugated polymer, poly(3-hexylthiophene) (P3HT). Although P3HT and other conjugated polymers have been known to exhibit excellent schottky diode behaviour, [29][30][31] these materials have limited patternability and poor solvent resistance. This significantly hampers the ability to use them to fabricate organic diodes array on top of the patterned resistor cells.…”
Section: Doi: 101002/adma201104266mentioning
confidence: 99%
“…It has been demonstrated that using an ITO surface coated with a buffer layer as the anode results in enhanced device performance [31]. The external quantum efficiency of polymer photovoltaic (PV) cells is greatly improved when PEDOT:PSS is used as a buffer layer [32].…”
Section: Transition Metal Oxides As Hole Buffer Layers In Organic Phomentioning
confidence: 99%